MINAT DAN KEBIASAAN BELAJAR TERHADAP PRESTASI BELAJAR MATA PELAJARAN AKUNTANSI SISWA KELAS XI IPS SMA NEGERI 1 PATAIANROWO NGANJUK - GALIH ARIWASESO W N (Jurnal Pendidikan Akuntansi (JPAK), 2013)
The research was conducted among secondary school students Nganjuk Patianrowo N 1. Research is explanatory research. The population of this study class XI IPS SMA N 1 Patianrowo Nganjuk Academic Year 2011/2012 and show as much as 105 students. Data was collected through questionnaire and method of documentation .. Test the validity of the technique of product-moment analysis and reliability testing using Cronbach's alpha. Test requirements analysis through test for normality, multicollinearity, heteroscedasticity, and autocorrelation. In addition, the data were collected and analyzed using descriptive analysis the percentage of multiple regression analysis. The results of this study indicate: (1) there is a positive and significant interest in achieving learning in Accounting Education, there is a positive and significant impact Habits learning of learning achievement in Accounting and the interests of positive impact significant learning, habit learning, learning achievement in Accounting. Keywords: Interest in learning, learning habits and learning achievements.